Keberpihakan Media Online dalam Konflik Kepemimpinan Lokal: Analisis Wacana Kritis Roger Fowler - Fitriyani, Lia; Anshori, Dadang S.; Kurniawan, Khaerudin (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
Local leadership often causes turmoil and conflict, especially between regional heads and their deputies. This was recorded on Instagram @indramayuterkini and @indramayuinfo as local online media which reported on the conflict between the Regent and Deputy Regent of Indramayu. This research aims to describe the alignment of the two local online media through the dimensions of vocabulary and grammar. This research uses a descriptive qualitative method with a critical discourse analysis approach according to the Roger Fowler model to analyze media partiality from aspects of vocabulary and grammar. The data analyzed were 3 news texts from Instagram Uploads @indramayuterkini and 3 news texts from @indramayuinfo during the period 14 February 2023–2 March 2023. The results of the research showed that the vocabulary and grammar used by local online media on Instagram @indramayuterkini tended to be cornering and limiting public view of the other party. On the other hand, the @indramayuterkini media is trying to build a positive narrative for the Regent of Indramayu. The opposite happened to the media @indramayuinfo which tended to use positive vocabulary and grammar toward the Deputy Regent of Indramayu. However, the other party is actually narrated through a cornering narrative. From the result of this research, it can be concluded that the local online media @indramayuterkini shows siding with the Regent of Indramayu, while @indramayuinfo shows siding with the Deputy Regent of Indramayu.